2022
DOI: 10.1051/bioconf/20225305001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of pesticide usage on grape yeast

Abstract: For the conventional vineyard, reducing the pesticide usage is the most important issue for converting to organic vineyard. In order to study the effect of pesticide usage on grape yeast, an investigation were designed in vintage 2020, ten vineyards (include two organic vineyards) with different treatment frequency index (TFI) were chosen, and the yeast population counted by two method: cultivate method and the direct epifluorescence technique (DEFT). The results show, the grape yeast from Moldova exist the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…The VBNC state is described as dormant microorganisms with low metabolic activity and an inability to divide without additional recovery attempts [51]; this was mostly studied in bacteria. However, recent studies on yeast reported the presence of VBNC under various stress factors such as pesticides [52], high phenol concentrations [53], sulfites [54], and isomerized hop extract [55] in varying degrees, including up to a complete loss of the culturability of the yeast population. Further investigation is to be carried out to confirm the presence of the VBNC state in S. cerevisiae CCM 9181 exposed to simulated gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The VBNC state is described as dormant microorganisms with low metabolic activity and an inability to divide without additional recovery attempts [51]; this was mostly studied in bacteria. However, recent studies on yeast reported the presence of VBNC under various stress factors such as pesticides [52], high phenol concentrations [53], sulfites [54], and isomerized hop extract [55] in varying degrees, including up to a complete loss of the culturability of the yeast population. Further investigation is to be carried out to confirm the presence of the VBNC state in S. cerevisiae CCM 9181 exposed to simulated gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The microflora involved in natural fermentation originates from grape berries as well as the winery environment and equipment. The composition of yeast species on grape berries is influenced by various biotic and abiotic factors such as grape variety, weather conditions, and viticultural practices [6,15,16,29]. Non-Saccharomyces yeasts, including Hanseniaspora, Candida, Kluyveromyces, Metschnikowia, Pichia, Cryptococcus, and Rhodotorula, are predominantly found on grapes, while Saccharomyces genera are less prevalent [16].…”
Section: Introductionmentioning
confidence: 99%